Analisis Sistem Pengendalian Internal Atas Persediaan Barang Dagang Di UMKM Kepripunyecerite - Angela Wulandari; Dyandra Sastra Wardani; Felita Jekri; Isrania Isrania; Meilin Meilin; Natalie Ernantonio (Jurnal Ilmiah Raflesia Akuntansi, 2025)
— MSMEs are small, micro and medium enterprises. The internal control system for inventory of goods in MSMEs is very important to ensure the availability of goods and meet consumer needs as a form of good service and maintaining the image of the MSMEs they own. Kepripunyecerite UMKM is a business that sells clothes as souvenirs that depict the identity of the Riau Islands Province. This business is located at Raja Haji Fisabilillah Airport on the second floor, precisely before the aircraft passenger departure gate, Penyengar Island, SRI Bintan Pura International Harbor, Dekranasda, Bintan Island. This business has been underway for two years. The problem of this research is what the internal control system is for the inventory of Kepripunyecerite MSME goods. The aim of this research is to determine the internal control system for the inventory of Kepripunyecerite MSME goods. The method used in this research is analysis based on information about social phenomena. Data Collection Techniques The data collection technique for this research is using library study techniques. Data Analysis Techniques The data analysis techniques for this research are: 1. Looking for phenomena 2. Looking for references. 3. Analyze the data. 4. Make conclusions. Based on the research conducted, results were found: 1. Kperipunyecerite MSMEs have an internal control system over inventory. 2. The Kepripunyecerite MSME internal control system brings benefits to MSME owners. 3. There are problems or shortages in inventory, namely capital and inventory.